STRATEGI GURU DALAM PEMETAAN POTENSI DIRI PESERTA DIDIK DI SEKOLAH DASAR - Wahyudi, Nanang Gesang (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This study focuses on mapping the self-potential of elementary and Islamic elementary school students (SD/MI) in Banjarnegara. Recognizing students' potential is important to help them develop interests, talents, and abilities, which positively impact their motivation to learn and self-confidence. The aim of this study is to explore the strategies used by teachers in mapping students' potential and to identify the challenges encountered in this process. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation at three schools: SD N 4 Pucungbedug, SD 4 Muhammadiyah Banjarnegara, and MI Cokroaminoto Kesenet. The findings show that teachers use various methods, such as direct observation, interviews, talent tests, home visit and grade analysis to identify students' potential. In activities focused on potential development, teachers engage students in extracurricular activities and competitions that match their abilities. However, challenges include limited time, a lack of teacher training and communication issues with parents.